Hiding in plain sight: epigraphic reuse in the temple-church at Aphrodisias - Sitz, Anna Marie (Journal of late antiquity, 2019)
Around 500 ce, the magnificent Temple of Aphrodite at Aphrodisias (Turkey) was deconstructed and rebuilt as an even larger church. During this process, several ancient inscriptions from the temple and from elsewhere, including building dedications and records of column donations, were incorporated into the new Christian sacred space. Previous studies of the temple-church have fixated on the original, Roman-period texts of the inscriptions and their historical contexts, to the exclusion of exploring their late antique reuse, the selective erasures that took place, and the potential meanings that these older texts, which were still legible to educated Greek-speaking viewers, may have held for the Christianizing city. By documenting the display of these older inscriptions in the architectural spaces of the temple-church, I argue that they continued to impart to the people of Aphrodisias a conception of their shared civic history centered on local elites and connections with distant Roman rulers. Moreover, the viewing of these older inscriptions in conjunction with the late antique graffiti in the church highlights the change in euergistic and epigraphic habits in Late Antiquity and reveals the democratization of commemorative practice in the early Christian period.
Gesehen am 10.09.2019